Togo : First Review under the Extended Credit Facility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Togo's First Review Under the Extended Credit Facility (ECF) Arrangement. Program implementation under the ECF-supported program has been good. All quantitative performance criteria and prior actions were met as well as four out of five structural benchmarks. The fiscal consolidation envisaged under the ECF-supported program has begun. The primary deficit improved from an annual average of about 6 percent of GDP in 2013-16 to a surplus of 1.4 percent of GDP in the first half of 2017, due primarily to expenditure rationalization and the halting of non-orthodox financing of public investment. The IMF staff supports the completion of the first ECF review as most quantitative targets, prior actions, and structural benchmarks have been met.